Method for synthesizing MWW framework-type molecular sieves
Patent Information
- Application Number
- JP2023553242
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-13
- Filing Date
- 2022-03-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-03-02
AI Technical Summary
Existing methods for synthesizing MWW framework type molecular sieves face challenges in achieving a balance between high external surface area and micropore volume, which is crucial for catalytic performance in applications like alkylation, particularly on a commercial scale.
A method involving a synthesis mixture with specific molar ratios and the inclusion of poly(diallyldimethylammonium chloride) (PDDA) as a cationic polymer, along with controlled crystallization conditions, to produce MWW framework type molecular sieves with enhanced external surface area and micropore volume.
The method results in MWW framework type molecular sieves with increased external surface area and micropore volume, improving catalytic performance by enhancing accessibility to surface pockets, particularly in aromatic alkylation processes.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of U.S. Provisional Patent Application No. 63 / 155990, filed March 3, 2021, and European Patent Application No. 21167971.7, filed April 13, 2021, each of which is incorporated by reference in its entirety. The present invention relates to a novel method for the synthesis of MWW framework type molecular sieves and to the molecular sieves so produced. [Background technology]
[0002] Molecular sieve materials, both natural and synthetic, have been demonstrated in the past to have catalytic properties for various types of hydrocarbon conversion reactions. Certain molecular sieves, such as zeolites, AlPO, and mesoporous materials, are ordered porous crystalline materials with well-defined crystal structures as determined by X-ray diffraction (XRD). Although some molecular sieves are ordered to produce specific identifiable XRD patterns, they are not strictly crystalline. Within certain molecular sieve materials, there may be numerous cavities, which may be interconnected by many channels or pores. These cavities and pores are uniform in size within a particular molecular sieve material. Because the dimensions of these pores are such that they accept the adsorption of molecules of certain dimensions while rejecting molecules of larger dimensions, these materials have become known as "molecular sieves" and are utilized in a variety of industrial processes.
[0003] Such molecular sieves include a wide variety of positive ion-containing crystalline silicates, both natural and synthetic. These silicates can be viewed as a three-dimensional framework of SiO4 tetrahedra and oxides of periodic group 13 elements (e.g., AlO4) tetrahedra. The tetrahedra typically share corners through oxygen atoms, and the electrical valence of the tetrahedra containing group 13 elements (e.g., aluminum, gallium, or boron) is charge balanced by the inclusion of cations, such as protons, alkali metal or alkaline earth metal cations. Typically, zeolite synthesis involves hydrothermal crystallization from a synthesis mixture that contains sources of all the components present in the zeolite, such as silica, but also sources such as alumina, and often also a structure directing agent and / or a source of hydroxide or fluoride ions. The synthesis mixture is often obtained by treating aluminate and silicate solutions with compounds that act to cleave Si-O bonds, thus providing Si to the growing crystals and in some cases destroying the amorphous structure. Hydroxides (OH - ) sources are often used to assist in the cleavage of Si-O bonds. Zeolite synthesis also commonly employs structure directing agents (SDAs), particularly organic molecular structure directing agents, to help promote the formation of crystals with the desired structure. Typically, zeolite crystals form around the structure directing agent, and once crystallization is complete, the structure directing agent occupies the pores in the zeolite. Thus, the "as-synthesized" zeolite contains the structure directing agent in its pores, and as a result, after crystallization, the "as-synthesized" zeolite is typically subjected to a calcination step to remove the structure directing agent. In many catalytic applications, it is also desired to include metal cations, such as metal cations from groups 2 to 15 of the Periodic Table of Elements, within the molecular sieve structure. This is typically achieved by ion exchange treatment. The formation of the desired zeolite structure can also be aided by adding seed crystals to the synthesis mixture. Seeding the molecular sieve synthesis mixture can provide beneficial effects that may include, for example, control of product particle size, accelerated synthesis, improved selectivity to desired structure types, and avoidance of the need for organic structure directing agents.
[0004] Molecular sieves such as zeolite crystalline structures have found widespread use in refining and other processes for manipulating petroleum streams. Some zeolite applications are catalytic in nature, while others focus on the ability of zeolites to selectively adsorb molecules within gas streams.
[0005] MWW-type molecular sieves are a type of zeolite that is useful in industrial processes, including, for example, in catalysis. Some members of the MWW zeolite family are the active components of commercial catalysts for processes such as alkylation. MCM-22 has been successfully used on a commercial scale in the alkylation of benzene to produce cumene. Zeolitic materials designated by the IZA-SC as being of MWW topology are multi-layered materials with two pore systems resulting from the presence of both 10-membered and 12-membered rings. Thus, MWW molecular sieves can be both microporous and mesoporous. As used herein, the term microporous is used to denote materials with pores having diameters less than 1.5 nm, and mesoporous is used to denote materials with pores having diameters between 1.5 nm and 50 nm. Based on their 10-ring internal pore system, MWW framework zeolites are generally considered to be medium pore size zeolites with pore sizes between about 5 Å and less than about 7 Å. However, the 12-ring surface pockets are not in communication with the 10-ring internal pore system, which may impart some properties more similar to alkylation catalysts of large pore zeolites such as mordenite.
[0006] Molecular sieves having an MWW framework structure are commonly referred to as "MWW family molecular sieve materials." As used herein, the term "MWW family molecular sieve materials" includes one or more of the following: (i) Molecular sieves made from common primary crystal building block unit cells, the unit cells having an MWW framework topology. (A unit cell is a spatial arrangement of atoms that, when arranged in three dimensional space, represents a crystal structure. Such crystal structures are discussed in "Atlas of Zeolite Framework Types", Fifth edition, 2001, which is incorporated by reference in its entirety; (ii) molecular sieves made from common secondary building blocks, two-dimensional juxtapositions of such MWW framework topology unit cells forming a monolayer one unit cell thick, preferably 1c-unit cell thick; (iii) molecular sieves made from common secondary building blocks, which are layers of one or more unit cell thicknesses, where the layers of two or more unit cell thicknesses are formed by stacking, packing, or bonding at least two monolayers of one unit cell thickness. The stacking of such secondary building blocks may be regular, irregular, random, or any combination thereof; (iv) Molecular sieves made from any regular or random two- or three-dimensional combination of unit cells having the MWW framework topology.
[0007] The MWW family molecular sieve materials are characterized by having XRD patterns that include d-spacing maxima at 12.4±0.25, 3.57±0.07, and 3.42±0.07 Angstroms (either calcined or as-synthesized). The MWW family molecular sieve materials may also be characterized by having XRD patterns that include d-spacing maxima at 12.4±0.25, 6.9±0.15, 3.57±0.07, and 3.42±0.07 Angstroms (either calcined or as-synthesized). The XRD data used to characterize the molecular sieves is obtained by standard techniques using a diffractometer equipped with a copper K-alpha doublet as the incident light and a scintillation counter and associated computer as the collection system. Materials belonging to the MWW family include MCM-22 (described in U.S. Pat. No. 4,954,325); PSH-3 (described in U.S. Pat. No. 4,439,409); SSZ-25 (described in U.S. Pat. No. 4,826,667); ERB-1 (described in European Patent No. 0293032); ITQ-1 (described in U.S. Pat. No. 6,077,498); ITQ-2 (described in International Patent Application Publication No. WO 97 / 17290); ITQ-30 (described in International Patent Application Publication No. WO 2005118476); MCM-36 (described in U.S. Pat. No. 5,250,277); MCM-49 (described in U.S. Pat. No. 5,250,277); No. 5,236,575; MCM-56 (described in U.S. Pat. Nos. 5,362,697, 5,827,491, and 5,453,554); EMM-10 (described in U.S. Pat. No. 8,110,176), EMM-10-P (described in U.S. Pat. No. 7,959,599), EMM-12 (described in International Patent Application Publication No. WO2010 / 021795), EMM-13 (described in International Patent Application Publication No. WO2010 / 014406), and MCM-22 family materials (described in U.S. Pat. No. 7,842,277). Also included are UZM-8 (described in U.S. Pat. No. 6,756,030); and UZM-8HS (described in U.S. Pat. No. 7,713,513). The entire contents of the above patents and patent applications are incorporated herein by reference. WO2007 / 094937 discloses a method for producing MCM-22 family molecular sieves.WO 2015 / 112293 discloses a method for making molecular sieves with MWW framework structure using precipitated aluminosilicates.
[0008] MWW-type zeolites have a layered three-dimensional structure, with each two-dimensional layer being approximately 1-2 nm thick. Within the MWW family, many individually defined materials exhibit different stacking arrangements of separate lamellar bodies. Various strategies that have been utilized to obtain different members of the MWW family are reviewed in "Lamellar MWW-Type Zeolites: Toward Elegant Nanoporous Materials", A. Schwanke et al., Appl. Sci. 2018, 8, 1636, the contents of which are incorporated herein by reference. For example, MCM-22 can be formed via a precursor (P)MCM-22 that contains the structure directing agent (SDA) hexamethyleneimine (HMI) sandwiched between the individual lamellar bodies, with hydrogen bonds between the HMI molecules and the silanol groups on the zeolite surface holding the lamellar bodies in place. Calcination removes the HMI molecules and condenses the silanol groups, thereby forming the three-dimensional MCM-22. A three-dimensional analogue of MCM-22, designated MCM-49, can be formed by direct crystallization from a gel mixture by increasing the relative proportion of alkali metal (sodium) in the composition, again using HMI as the SDA. "Zeolite MCM-49: A Three-Dimensional MCM-22 Analogue Synthesized by in situ Crystallization", SL Lawton et al., J. Phys. Chem., 1996, 100, 3788-3798, discloses the synthesis and characterization of MCM-22, (P)MCM-22 and MCM-49. (P)MCM-22 is disclosed to be synthesized when the reaction mixture has an organic template / inorganic cation (alkali metal) ratio of greater than 2.0, while MCM-49 forms when the molar ratio is less than 2.0. MCM-22 and MCM-49 were found to be structurally very similar, except for the larger unit cell c-parameter of MCM-49, suggesting an increase in the interlayer distance in the layered structure. Increasing the proportion of alkali metals in the reaction mixture led to increased aluminum incorporation into the zeolite framework.For MCM-49, with HMI as SDA, crystallite framework Si / Al2 ratios of 17 to 22 were reported. MCM-22 zeolites with Si / Al ratios ranging from 9 to 46 (corresponding to Si / Al2 ratios of 18 to 92) are disclosed in "Synthesis of MCM-22 zeolites of different Si / Al ratio and their structural, morphological and textural characterisation", C. Delitala et al., Microporous and mesoporous Materials, volume 118, issues 1-3, 2009, pages 1-10.
[0009] The preparation of MCM-22 from a reaction mixture using NaOH or KOH as mineralizers and HMI as SDA is disclosed in "Synthesis and characterization of MCM-22 and MCM-49 zeolites", D. Vuono et al., Studies in Surface Science and Catalysis, 154, 2004, 203-210. In this work, MCM-49 zeolite is also reported, but only NaOH as mineralizer was used (using KOH, only (P)MCM-22 could be obtained).
[0010] The preparation of nanosized MCM-22 zeolite from a synthesis mixture containing colloidal silica as a Si source and a cationic polymer (poly(diallyldimethylammonium) (PDDA) chloride) is disclosed in "Synthesis of the nanosized MCM-22 zeolite and its catalytic performance in methane dehydro-aromatization reaction", X. Yin et al., Catalysis Communications, volume 43, 2014, pages 218-222. PDDA chloride was added to act as a protective agent and avoid self-aggregation of the synthetic colloids.
[0011] MCM-56 is an MWW family zeolite with partial layer disorder that forms as an intermediate to MCM-49 (see A. Schwanke et al.). Each layer in MCM-56 is porous and has a framework structure closely related to that of MCM-22 and other MCM-22 family members. MCM-56 is isolated by stopping the reaction used to form MCM-49 midway through the crystallization process. If the crystallization were allowed to continue, the initially exfoliated and randomly packed MCM-56 sheets (with MCM-22 topology and one 25 Å thick unit cell) would gradually begin to organize into a three-dimensional framework ordered in the c-direction, which would formally become the zeolite MCM-49. The formation of MCM-56 presents unique challenges, especially on a large scale, as it is a primary product and may undergo further changes during the manufacturing process. For example, while careful control of crystallization conditions may be manageable on a laboratory scale, determining the exact time to stop crystallization and therefore isolate useful quantities of the intermediate zeolite can be challenging on a commercial scale. WO 2013 / 048636 discloses a method for producing high quality porous crystalline MCM-56 material.
[0012] MWW zeolites are characterized by a high aluminum content. A high aluminum content is important for high activity in catalytic processes. Each aluminum center in the accessible portion of the zeolite provides an acidic site that can provide catalytic activity. The higher the aluminum content, the more acidic the zeolite is, and therefore the higher the activity. When the aluminum centers are located in the zeolite pores, the size and shape of the pores can affect the selectivity and activity. For example, reactant molecules that can more easily access the pores may undergo catalytic reactions in preference to molecules that have a size and / or shape that inhibits access to the pores. This can provide advantages and limitations to the zeolite catalyst. For example, when aluminum centers are incorporated into sites in relatively small pores, the resulting zeolite catalyst can provide high selectivity for reactions with small reactant molecules, but also relatively low activity (even with smaller molecules because the reaction is slower, for example, due to the time it takes for the reactant molecules to enter and exit the pores). Such catalysts may not be effective in catalyzing reactions involving larger reactant molecules, such as aromatic molecules. In MWW zeolites, aluminum centers located in the 12-ring surface pores provide promising catalytic sites accessible to larger molecules, while aluminum centers located in the internal pore network in the 10-ring may be accessible only to smaller molecules. The mixed 10-ring / 12-ring structure of MWW zeolites may provide suitable catalysts for use with a wider range of reactant molecules, depending on where the aluminum is incorporated within the zeolite framework.
[0013] Although many methods exist for synthesizing MWW framework type molecular sieves, there remains a need for additional MWW zeolites having improved properties or combinations of improved properties, such as high external surface area combined with high micropore volume (high mesoporosity). Summary of the Invention
[0014] The present invention provides a method for synthesizing a molecular sieve of MWW framework type, the method comprising preparing a synthesis mixture capable of forming a molecular sieve of MWW framework type, the synthesis mixture comprising water, a silicon source, a source of a trivalent element X, a structure directing agent R, a source of an alkali metal or alkaline earth metal cation M, a source of poly(diallyldimethylammonium) cation (PDDA), optionally a source of a pentavalent element Z, optionally a source of hydroxide ions, and optionally a seed crystal. The synthesis mixture has the following molar ratio composition: Si:X2=8 to less than 30, H2O:Si=5 to less than 50, M:Si=0.05 to 1.0, R:Si=0.05 to 1.0. The synthesis mixture comprises a source of PDDA in an amount of 0.01 to less than 1.0 wt. %, based on the weight of the synthesis mixture. The method further comprises heating the synthesis mixture under crystallization conditions for a time sufficient to form crystals of the MWW framework type molecular sieve, the crystallization conditions comprising a temperature between 80° C. and 225° C., and recovering the crystals of the MWW framework type molecular sieve from the synthesis mixture.
[0015] It has been found that the presence of PDDA in the zeolite synthesis mixture aids in the formation of MWW-type molecular sieves with high external surface area along with high micropore volume. In particular, the resulting MWW-type molecular sieves are believed to have an external surface area in the range of that of previously known MCM-56 zeolites, while the MWW-type molecular sieves have a higher micropore volume, approximating that of previously known MCM-49 zeolites, in contrast to those previously known. Without wishing to be bound by theory, the inventors believe that the PDDA used in the synthesis mixture acts as a zeolite growth modifier. Since the accessibility of the surface pockets of the MWW-type molecular sieves is of great importance to their catalytic performance, for example in applications such as alkylation, an increase in the external surface area is particularly advantageous, while the retention or increase in microporosity is fundamental to shape the selective catalysis by the molecular sieves.
[0016] The present invention also provides molecular sieves of MWW framework type obtainable or produced by the synthesis method of the present invention. The present invention relates to a composition having a molar relationship: (n) SiO2:X2O3, where X is a trivalent element selected from the group consisting of aluminum, boron, gallium, and mixtures thereof, and n is the number of moles of SiO2 per mole of X2O3, which varies from 8 to less than 30; 2 External surface area (S ext ); and 0.13 cm 3 / g or more for micropore volume (V micro ) in its calcined anhydrous form. The present invention further provides a catalyst comprising the MWW framework type molecular sieve of the present invention. The present invention further provides a process for hydrocarbon chemical conversion comprising the step of contacting a hydrocarbon feedstock with the catalyst of the present invention, hi one embodiment, the catalytic process is alkylation, such as aromatic alkylation. These and other features and characteristics of the present disclosure, as well as its advantageous applications and / or uses, will become apparent from the following detailed description, it being understood, of course, that features described in connection with one aspect of the invention may be incorporated in other aspects of the invention. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 shows XRD spectra of Comparative Examples 1-2 and Examples 3-5 in their as-synthesized forms. [Figures 2a-2e] FIG. 2 is a diagram showing scanning electron microscope (SEM) images of Comparative Examples 1 and 2 and Examples 3 to 5, respectively. [Diagram 3] FIG. 2 is a diagram showing 27Al NMR spectra of Comparative Examples 1 to 2 and Example 4. [Figure 4] FIG. 1 is a diagram showing N2 physical adsorption isotherms of Comparative Examples 1 to 2 and Example 4. [Diagram 5] FIG. 1 shows as-prepared thermogravimetric analysis of Comparative Example 1 and Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The method of synthesizing a MWW framework type molecular sieve in accordance with the present invention comprises preparing a synthesis mixture in accordance with conventional techniques, except that the synthesis mixture comprises at least a source of poly(diallyldimethylammonium chloride) cation (PDDA) and the synthesis mixture has a Si:X2 molar ratio of less than 30 and a H2O:Si molar ratio of less than 50. The method of synthesizing a molecular sieve in accordance with the present invention further comprises crystallizing the molecular sieve in accordance with conventional techniques and isolating the molecular sieve in accordance with conventional techniques.
[0019] synthetic mixture As mentioned above, the synthesis mixture can be prepared by conventional methods. The components of the synthesis mixture can be combined in any order. The synthesis mixture of the present invention includes a source of cationic polymer, specifically poly(diallyldimethylammonium) cation (PDDA). The source of PDDA is present in the synthesis mixture of the present invention in an amount of less than 0.01-1.0 wt%, typically 0.02-0.7 wt%, preferably less than 0.04-0.7 wt%, such as 0.05-0.5 wt%, based on the weight of the synthesis mixture. Without wishing to be bound by theory, the inventors believe that the PDDA acts as a zeolite growth modifier, resulting in a controlled structure of the zeolite. More specifically, the present inventors have surprisingly found that the presence of PDDA in the zeolite synthesis mixture of the present invention aids in the formation of MWW type molecular sieves having high external surface area with high micropore volume, the resulting MWW type molecular sieves having an external surface area in the range of that of the previously known MCM-56 zeolite, while having a higher micropore volume, approximating the micropore volume of the previously known MCM-49 zeolite, in contrast to that previously known. This combination of high external surface area with high micropore volume is particularly advantageous, since it results in higher accessibility to the surface pockets of the MWW type molecular sieve, while retaining selectivity (which is of significant importance in its catalytic performance, e.g., in applications such as alkylation).
[0020] The PDDA source may be selected from at least one of PDDA chloride and / or PDDA hydroxide, such as PDDA chloride. The molecular weight (Mw) of the PDDA source is typically in the range of 50,000 to 1,000,000 grams per mole, preferably 100,000 to 800,000, such as 150,000 to 600,000 or 200,000 to 500,000, and specific examples including a PDDA source have an Mw of 200,000 to 350,000 or 400,000 to 500,000.
[0021] The synthesis mixture further comprises a structure directing agent R. It will be understood that any structure directing agent suitable for forming MWW-type molecular sieves may be used. Suitable structure directing agents include cyclopentylamine, cyclohexylamine, cycloheptylamine, hexamethyleneimine (HMI), heptamethyleneimine, homopiperazine, and combinations thereof. Additionally or alternatively, the structure directing agent may be a diquat salt or diquat hydroxide, such as a pentamethonium salt or hydroxide (e.g., pentamethonium bromide or pentamethonium hydroxide), a hexamethonium salt or hydroxide (e.g., hexamethonium bromide or hexamethonium hydroxide), and / or a heptamethonium salt or hydroxide (e.g., heptamethonium bromide or heptamethonium hydroxide). Additionally or alternatively, the structure directing agent may be a salt or hydroxide of diethyl-dimethylammonium, or a salt or hydroxide of N,N,N-trimethyl-1-adamantanammonium, or a salt or hydroxide of N,N,N-trimethyl-2-adamantanammonium, such as the chloride, bromide or hydroxide. Preferably, the structure directing agent R is hexamethyleneimine (HMI). The structure directing agent R is present in a molar ratio to silicon R:Si of 0.05 to 1.0, and may also be 0.08 to 0.8, such as 0.1 to 0.5 or 0.1 to 0.3, for example 0.15 to 0.25, or even 0.16 to 0.20.
[0022] The synthesis mixture comprises one or more sources of trivalent element X, such as aluminum, boron, and / or gallium, preferably X comprises Al, more preferably X is Al. Suitable sources of trivalent element X that can be used to prepare the synthesis mixture depend on the element X selected. In embodiments where X is aluminum, suitable Al sources (e.g. aluminum oxide) for use in the present method include aluminum salts, especially water-soluble salts, such as aluminum sulfate, aluminum nitrate, aluminum hydroxide, sodium aluminate, and aluminum alkoxides, such as aluminum isopropoxide, as well as hydrated aluminum oxides, such as boehmite, gibbsite, and pseudoboehmite, and mixtures thereof. In embodiments where X is boron, B sources include boric acid, sodium tetraborate, and potassium tetraborate. Sources of boron tend to be more soluble than sources of aluminum in hydroxide-mediated synthesis systems. In embodiments where X is gallium, the Ga source includes sodium gallate, potassium gallate, and gallium salts such as gallium chloride, gallium sulfate, and gallium nitrate. Preferably, X is Al and the source of aluminum in the synthesis mixture includes Al2O3, for example the source of aluminum is sodium aluminate. The synthesis mixture has a Si:X2 molar ratio of at least 8, preferably at least 10, more preferably at least 12, most preferably at least 13, such as at least 15 or at least 16 or at least 17. The synthesis mixture has a Si:X2 molar ratio of less than 30, particularly at most 28 or even at most 25. The synthesis mixture has a Si:X2 molar ratio of 8 to less than 30, such as at most 10 to less than 30 or at most 12 to less than 30, such as at most 15 to 25. In a particularly preferred embodiment, X is Al.
[0023] Suitable Si sources (e.g. silicon oxide) for use in the present method include silicates, such as tetraalkyl orthosilicates, such as tetramethyl orthosilicate, fumed silicas, such as Aerosil® (available from Degussa) and Cabosil® (fumed silica available from DMS), precipitated silicas, such as Ultrasil® and Sipernat® 340 (available from Evonik), alkali metal silicates, such as potassium silicate and sodium silicate, and aqueous colloidal suspensions of silica, such as those sold by EI du Pont de Nemours under the trade name Ludox®, preferably silicates, fumed silica, precipitated silica and alkali metal silicates. In certain embodiments, the silicon source comprises SiO2, preferably the silicon source is SiO2, such as in the form of fumed silica, precipitated silica or aqueous colloidal suspensions of silica, most often fumed silica or precipitated silica.
[0024] Alternatively or in addition to the previously described sources of Si and Al, sources containing both the elements Si and Al can also be used as sources of Si and Al. Examples of suitable sources containing both the elements Si and Al include amorphous silica-alumina gel or dry silica-alumina powder, silica-alumina, clays such as kaolin, meta-kaolin, and zeolites, particularly aluminosilicates such as synthetic faujasites and ultrastable faujasites, e.g. USY, beta or other large to medium pore zeolites.
[0025] The synthesis mixture may include one or more sources of a pentavalent element Z, such as phosphorus. A suitable source of the pentavalent element Z depends on the element Z selected. Preferably, Z is phosphorus. Suitable sources of phosphorus include phosphoric acid, organic phosphates, such as triethyl phosphate and tetraethyl-ammonium phosphate, and aluminophosphates. Alternatively, the synthesis mixture does not contain the pentavalent element Z.
[0026] The synthesis mixture comprises one or more sources of alkali or alkaline earth metal cations M, M being preferably selected from the group consisting of sodium, potassium, lithium, rubidium, calcium, magnesium and mixtures thereof, preferably sodium and / or potassium, more preferably sodium. The sodium source, if present, may be sodium hydroxide, sodium aluminate, sodium silicate, sodium aluminate or a sodium salt, such as NaCl, NaBr or sodium nitrate. The potassium source, if present, may be potassium hydroxide, potassium aluminate, potassium silicate, potassium salt, such as KCl or KBr or potassium nitrate. The lithium source, if present, may be lithium hydroxide or a lithium salt, such as LiCl, LiBr, LiI, lithium nitrate or lithium sulfate. The rubidium source, if present, may be rubidium hydroxide or a rubidium salt, such as RbCl, RbBr, RBI or rubidium nitrate. The calcium source, if present, may be calcium hydroxide, for example. The magnesium source, if present, may be magnesium hydroxide, for example. The alkali or alkaline earth metal cation M may also be present in one or more sources of trivalent element X, such as sodium aluminate, sodium tetraborate, potassium tetraborate, sodium gallate, potassium gallate, etc., and / or in one or more sources of Si, such as potassium silicate and sodium silicate, etc. The synthesis mixture comprises a source of alkali or alkaline earth metal cation M, in a M:Si molar ratio of 0.05 to 1.0, preferably 0.08 to 0.5, more preferably 0.1 to 0.3, such as 0.1 to 0.25, or greater than 0.1 and less than 0.18.
[0027] The synthesis mixture may include one or more sources of hydroxide ions, such as alkali metal hydroxides, alkaline earth metal hydroxides, ammonium hydroxide, and mixtures thereof; such as sodium hydroxide, potassium hydroxide, lithium hydroxide, rubidium hydroxide, calcium hydroxide, magnesium hydroxide, ammonium hydroxide, and mixtures thereof; more frequently sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonium hydroxide, and mixtures thereof; most frequently sodium hydroxide and / or potassium hydroxide. Hydroxide may also be present through the use of aluminum hydroxide as a counterion of the structure directing agent R, as a counterion of the PDDA cationic polymer, or as a source of Al. Alternatively, the synthesis mixture may be free of a hydroxide source. The synthesis mixture may include a source of hydroxide ions selected from the group consisting of 0.05 to 1.0 OH - The hydroxide ion source is preferably KOH and / or NaOH, and the hydroxide ion source may be a hydroxide ion source having a molar ratio of 0.08 to 0.5, for example, 0.1 to 0.3, or 0.1 to 0.25, or may be greater than 0.1 and less than 0.18.
[0028] The synthesis mixture may contain 0.05 to 2, for example 0.1 to 1.5, for example 0.15 to 1 g of seed crystals. 種晶 / g (silicon source + source of trivalent element X). Any seed crystals may be of framework type MWW or of any other framework type that allows the synthesis mixture to form a molecular sieve of MWW framework type. For example, when the seed crystals comprise, and preferably consist of, MCM-49 and / or MCM-56 zeolites, the seed crystals may comprise a molecular sieve of framework type MWW. The seed crystals may be included in the synthesis mixture in the form of a colloidal suspension in a liquid medium such as water. As used herein, the expression "colloidal suspension" refers to a suspension containing discrete, finely divided particles dispersed in a continuous liquid phase; preferably, it refers to a suspension that is stable at ambient temperature (23°C) in the sense that no visible separation occurs or no sediment is formed for a period of time sufficient for the intended use, advantageously at least 10 hours, more advantageously at least 20 hours, preferably at least 100 hours, more preferably at least 500 hours. The maximum size of the particles for which the suspension remains stable (peptized) depends to some extent on their shape and on the nature and pH of the continuous medium as well as on the period for which the suspension must remain usable. The particles may be spherical or of other shape. If the particles are other than spherical, the dimensions given are their minimum dimensions. Colloidal seeds generally have an average diameter (or minimum dimension, which corresponds to the number average primary particle size determined by SEM for 100 or more particles) of 300 nm or less, particularly 200 nm or less, more particularly 100 nm or less, provided that the colloidal seeds form a stable suspension in the sense that no visible separation occurs or no sediment is formed for a period sufficient for the intended use. The production and use of colloidal seed suspensions in the synthesis of molecular sieves is disclosed, for example, in International Patent Application Publication Nos. WO 00 / 06493 and WO 00 / 06494.
[0029] The synthesis mixture comprises H2O and SiO2 in a H2O:SiO2 molar ratio of 5 to less than 50, particularly 5 to 40, more particularly 10 to 30, such as 15 to 25. In a preferred embodiment, the synthesis mixture comprises a structure directing agent R and a source of alkali metal or alkaline earth metal cation M in an R:M molar ratio of less than 2.5, preferably less than 2.0. Crystallization and Recovery Crystallization conditions in step (b) of the present method include a temperature of 80°C to 225°C, preferably 100°C to 200°C, more preferably 140°C to 180°C, such as 150°C to 170°C, for example 155°C to 165°C.
[0030] The time required to carry out crystallization varies. For example, at higher temperatures, crystallization times may be reduced. The crystallization conditions in step (b) of the method may include heating for a period of from 1 to about 800 hours, such as from about 10 to less than 600 hours, in particular from about 24 to 140 hours, for example from about 40 to about 90 hours. The crystallization time can be established by methods known in the art, such as by sampling the synthesis mixture at various times and determining the yield and x-ray crystallinity of the precipitated solid. Crystallization can be carried out in any suitable reaction vessel, such as, for example, a polypropylene jar or Teflon bottle, an acid digestion vessel, a Teflon-lined or stainless steel autoclave, a plow shear mixer, or a reaction kettle, preferably a polypropylene jar, a Teflon bottle, or a Teflon-lined or stainless steel autoclave.
[0031] The synthesis mixture may be vigorously stirred during step (b), e.g., the conditions during step (b) include stirring. The synthesis mixture may be stirred for at least a portion of step (b), e.g., throughout step (b). Alternatively, the synthesis mixture is not stirred during step (b), i.e., crystallization is carried out under static conditions. During step (b), the synthesis mixture may be heated with vigorous stirring provided by a mixing device that moves the mixture in a turbulent manner, such as occurs in a pitched blade turbine mixer. Other means of introducing vigorous stirring known to those skilled in the art may be utilized, such as pumping the synthesis mixture around a vessel holding the mixture. The purpose of the vigorous stirring is to aid in uniform mass and heat transfer throughout the synthesis mixture. The degree of vigorous stirring should be low enough to minimize shear-induced seed formation in the synthesis mixture. Vigorous stirring may be stopped once the synthesis mixture reaches a predetermined set temperature. Heating of the synthesis mixture may be continued after cessation of vigorous stirring. Alternatively, the temperature may be maintained at the temperature reached when vigorous stirring was stopped. It will be appreciated that after step (b), the synthesis mixture may be vigorously agitated (e.g., stirred). The synthesis mixture may be subjected to intermittent agitation while being heated, such that the synthesis mixture may be subjected to multiple static crystallization steps separated by vigorously agitated crystallization steps. For example, step (b) of the present method may be repeated after a step of heating the synthesis mixture under agitated crystallization conditions, said crystallization conditions comprising a temperature between 80°C and 225°C.
[0032] The crystallization conditions of step (b) may include a temperature equal to or greater than the effective nucleation temperature of the synthesis mixture. An effective nucleation temperature may be understood to be a temperature at which continued stirring of the heated zeolite synthesis mixture results in a significant reduction in the mass average crystal diameter of the resulting zeolite crystals, for example a reduction of 15 percent or more in the mass average crystal diameter of the resulting crystals. Preferably, the temperature of step (b) of the method is a temperature at which, when the synthesis mixture is stirred, stirring results in a reduction of the mass average crystal diameter of the resulting zeolite crystals of less than 10 percent, more preferably less than 5 percent, compared to the resulting zeolite crystals obtained from the corresponding non-stirred synthesis mixture. It will be understood that the effective nucleation temperature of the synthesis mixture depends on the composition of the synthesis mixture, which in turn is governed by the zeolite being prepared. The effective nucleation temperature can be ascertained by procedures known in the art, such as by x-ray detection of the presence of crystals larger than any seed level. The change in the synthesis mixture viscosity during the initial period can also be used to determine the onset of crystallization. The effective nucleation temperature is a function of the type of zeolite being prepared and can often be expressed as a temperature range rather than a single clearly defined temperature.
[0033] Typically, the molecular sieve product is formed in solution and can be recovered by standard means such as centrifugation or filtration. The isolated product can also be washed, recovered by centrifugation or filtration, and dried.
[0034] Molecular Sieve Processing As a result of the crystallization process, the recovered molecular sieve product contains within its pores at least a portion of the structure directing agent used in the synthesis. Preferably, the method additionally includes activating the molecular sieve to remove the structure directing agent from the molecular sieve and leave the active sites in the microporous channels of the molecular sieve open for contact with the feedstock. The activation process is typically accomplished by calcining or essentially heating the molecular sieve containing the template in the presence of an oxygen-containing gas. In some cases, it may be desirable to heat the molecular sieve in an environment with low or no oxygen concentration. This type of process can be used to partially or completely remove the structure directing agent from the intracrystalline pore system. In other cases, particularly with smaller structure directing agents, complete or partial removal from the sieve can be achieved by conventional desorption processes. Typically, the recovered molecular sieve is subjected to a calcination step which involves heating the material at a temperature of at least about 200°C, preferably at least about 300°C, more preferably at least about 370°C for at least 1 minute and generally less than 20 hours. While subatmospheric pressures can be utilized for the heat treatment, for reasons of convenience, atmospheric pressure is usually desired. The heat treatment can be carried out at a temperature up to about 925°C. For example, the heat treatment can be carried out in the presence of an oxygen-containing gas, e.g., in air and / or ozone, at a temperature of 300-600°C, e.g., 400-550°C, e.g., 500-550°C.
[0035] The molecular sieve may also be subjected to an ion exchange treatment, for example with aqueous ammonium salts such as ammonium nitrate, ammonium chloride, and ammonium acetate, to remove any remaining alkali metal and / or alkaline earth metal cations and replace them with protons, thereby producing the acid form of the molecular sieve. To the extent desired, the original cations, such as the alkali metal cations, of the as-synthesized material may be replaced with other cations by ion exchange. Preferred cations for replacement may include hydrogen ions, hydrogen precursors, such as ammonium ions, and mixtures thereof. The ion exchange step may be performed after the as-prepared molecular sieve is dried. The ion exchange step may be performed either before or after the calcination step. The molecular sieves may also be subjected to other treatments, such as steam treatment and / or washing with solvents, which are well known to those skilled in the art and are performed to adjust the properties of the molecular sieve as desired.
[0036] Once the molecular sieves are synthesized, they can be combined with other materials, such as binders and / or matrix materials that provide additional hardness to the final product, and formulated into a product composition. These other materials can be inert or catalytically active materials.
[0037] In particular, it may be desirable to incorporate the molecular sieve of the present invention or the molecular sieve produced by the method of the present invention into another material that is resistant to the temperatures and other conditions encountered during use. Such materials include synthetic or naturally occurring zeolites, as well as inorganic materials such as clays, silica and / or metal oxides, such as alumina, yttria, zirconia, gallium oxide, zinc oxide, and mixtures thereof. The metal oxides may be either naturally occurring or in the form of gelatinous precipitates or gels, including mixtures of silica and metal oxides. Naturally occurring clays that may be used include the montmorillonite and kaolin families, which include subbentonite, kaolin commonly known as Dixie, McNamee, Georgia, and Florida clays, or others whose main mineral elements are halloysite, kaolinite, dickite, nacrite, or anauxite. Such clays may be used in their original raw state as mined, or with subsequent calcination, acid treatment, or chemical conditioning. These binding materials are resistant to temperature and other conditions, such as mechanical wear, occurring in various hydrocarbon separation processes. Thus, the molecular sieves of the present invention or molecular sieves produced by the method of the present invention can be used in the form of extrudates together with a binding agent. They are typically bound by forming pills, spheres, or extrudates. The extrudates are typically formed by extruding the molecular sieve, optionally in the presence of a binding agent, and drying and calcining the resulting extrudates. Further processing, such as steam treatment and / or ion exchange, may be carried out if required. The molecular sieves are preferably at least 100 m 2 / g, e.g. at least 200m 2 / g, at least 300m 2 The binder may be combined with a binder having a surface area of 0.1 to 1.0 μm / g.
[0038] These materials may be incorporated into naturally occurring clays such as bentonite and kaolin to improve the crush strength of the product under commercial operating conditions. In addition to the materials previously mentioned, the molecular sieves of the present invention can be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, etc., as well as ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia.
[0039] The relative proportions of molecular sieve and inorganic oxide matrix can vary widely, with the molecular sieve content ranging from about 1 to about 100 weight percent of the composite, more typically from about 2 to about 95, and more typically from about 20 to about 90 weight percent, particularly when the composite is prepared in the form of an extrudate. Molecular Sieve The present invention also provides a molecular sieve of MWW framework type obtainable or produced by the process of the present invention.
[0040] In a further embodiment, the present invention also provides a compound having a calcined anhydrous form, the compound having the molar relationship: (n)SiO2:X2O3 wherein X is a trivalent element selected from aluminum, boron, and / or gallium, preferably X comprises at least aluminum, more preferably X is aluminum, and n is the number of moles of SiO2 per mole of X2O3, varying from 8 to less than 30, particularly at least 10, such as at least 12 or at least 14, such as up to less than 30, such as at most 26 or at most 24. It will be understood that the Si:X2 molar ratio is the molar ratio in the molecular sieve framework. Any suitable method can be used to verify the composition of the molecular sieve material, such as inductively coupled plasma optical emission spectroscopy (ICP-OES) analysis. Preferably, when X is Al, 27 Al NMR spectroscopy can be used to determine whether the Al detected in a molecular sieve sample is Al incorporated into the molecular sieve framework or Al that has been deposited on the material as an impurity. Aluminum outside the framework is 27It will be appreciated that Al NMR spectroscopy can be expected to show a signal having a chemical shift (δ) of around 0 ppm. 27 It is visible by Al NMR spectroscopy as a signal with a shift (δ) close to 50 ppm.
[0041] The MWW framework type molecular sieves of the present invention are characterized by a high external surface area along with a high micropore volume. Advantageously, the MWW framework type molecular sieve of the present invention, in its calcined and ion-exchanged form, has a molecular weight of 0.13 cm 3 / g, preferably at least 0.14 cm 3 / g, more preferably at least 0.15 cm 3 / g micropore volume (V micro ) The micropore volume (V micro ) is typically at most 0.2 cm 3 / g, more precisely at most 0.19 cm 3 / g, for example, at most 0.18 cm 3 / g, etc. Advantageously, the MWW framework type molecular sieve of the present invention, in its calcined and ion-exchanged form, has a molecular weight of at least 125 m. 2 / g, preferably at least 130m 2 / g, more preferably at least 135m 2 / g, most preferably at least 140m 2 / g, e.g. at least 145m 2 Nitrogen external surface area (S ext ) (also commonly referred to as mesopore surface area). The nitrogen external surface area (S ext ) is typically at most 200m 2 / g, more precisely at most 180m 2 / g, most specifically at most 165m 2 / g, for example, at most 160m 2 / g, etc.
[0042] S ext and V microA preferred method for obtaining σ is by applying a t-plot model to the N2 isotherm as referenced in Analytical Methods in Fine Particle Technology, P.A. Webb and C. Orr, Micrometrics Instrument Corporation, ISBN 0-9656783-0-X, the contents of which are incorporated herein by reference. The MWW framework type molecular sieve of the present invention, in its calcined and ion-exchanged form, has a molecular weight of 250-600, such as 300-550, for example 400-550 m 2 / g nitrogen Brunauer-Emmett-Teller (BET) total surface area (S tot ). The MWW framework type molecular sieve of the present invention, in its calcined and ion-exchanged form, has an S content of greater than 20%, preferably 22-50%, more preferably 25-35%. ext / S tot The ratio may be: The MWW framework type molecular sieves of the present invention are characterized by having XRD patterns that include d-spacing maxima at 12.4±0.25, 3.57±0.07, and 3.42±0.07 Angstroms (either calcined or as-synthesized). The MWW family molecular sieve materials may also be characterized by having XRD patterns that include d-spacing maxima at 12.4±0.25, 6.9±0.15, 3.57±0.07, and 3.42±0.07 Angstroms (either calcined or as-synthesized). The MWW framework type molecular sieve of the present invention, in its as-synthesized form, may have an X-ray diffraction pattern characteristic of MCM-49 as shown in Table 1 below: [Table 1]
[0043] The MWW framework type molecular sieve of the present invention, in its calcined form, may have an X-ray diffraction pattern characteristic of MCM-49 as shown in Table 2 below: [Table 2]
[0044] Relative strength is given in code terms: vs = very strong (60-100), s = strong (40-60), m = moderate (20-40) and w = weak (0-20). It will be understood by those skilled in the art that the MWW framework molecular sieves of the present invention may contain impurities such as amorphous materials; unit cells with non-MWW framework topologies (e.g., MFI, MTW, MOR, FER, quartz, tridymite or other density phases that may or may not affect the performance of the resulting catalyst); and / or other impurities (e.g., heavy metals and / or organic hydrocarbons). Typical examples of non-MWW framework molecular sieves that coexist with the MWW framework molecular sieves of the present invention are Kenyaite, EU-1, ZSM-50, ZSM-12, ZSM-48, ZSM-5, ferrierite, mordenite, sodalite, and / or analcine. Other examples are molecular sieves with EUO, MTW, FER, MOR, SOD, ANA, and / or MFI framework types. The MWW framework molecular sieves of the present invention are preferably substantially free of impurities. The term "substantially free of impurities" as used herein means that the MWW framework molecular sieve of the present invention preferably contains a low proportion (less than 50 wt%) of such impurities (or "non-MWW framework molecular sieves"), preferably less than 20 wt%, more preferably less than 10 wt%, even more preferably less than 5 wt%, and most preferably less than 1 wt%, the weight percent (wt%) value being based on the combined weight of the impurities and the pure phase MWW framework molecular sieve. The amount of impurities can be suitably determined by powder XRD, rotational electron diffraction, and / or SEM / TEM (e.g., different crystal morphology structures).
[0045] Use of molecular sieves The MWW framework type molecular sieves of the present invention may be used as adsorbents, such as to separate at least one component from a mixture of components in the gas or liquid phase having different adsorption characteristics for the molecular sieve. Thus, at least one component can be partially or substantially completely separated from a mixture of components having different adsorption characteristics for the molecular sieve by contacting the mixture with the molecular sieve to selectively adsorb one component.
[0046] The molecular sieves of the present invention can be used to catalyze a wide variety of chemical conversion processes, including many of current commercial / industrial importance. Examples of chemical conversion processes that are effectively catalyzed by molecular sieves, either alone or in combination with one or more other catalytically active materials, including other crystalline catalysts, include those that require catalysts with acid activity. Specific examples include: (1) Alkylation of aromatic hydrocarbons, such as benzene, using long chain olefins, such as C14 olefins, at a temperature of about 340° C. to about 500° C., at a pressure of about atmospheric pressure to about 200 atm, for about 2 hours. -1 ~ Approx. 2000 hours -1 and an aromatic hydrocarbon / olefin molar ratio of from about 1 / 1 to about 20 / 1 to provide long chain alkylaromatics which can be subsequently sulfonated to provide synthetic detergents; (2) Alkylation of aromatic hydrocarbons using gaseous olefins at a temperature of about 170°C to about 260°C, a pressure of about 20 to about 55 atm, and for 0.1 hours. -1 ~ approx. 20 hours -1 or the alkylation of benzene using ethylene to provide ethylbenzene, or the alkylation of benzene using ethylene at a temperature of about 10° C. to about 125° C., a pressure of about 1 to about 30 atmospheres, and a reaction time of about 5 hours. -1 ~ approx. 50 hours -1 Alkylation of benzene with propylene to provide cumene (isopropylbenzene) at reaction conditions including an aromatic hydrocarbon mass hourly space velocity (WHSV) of; (3) alkylation of a reformate containing sufficient amounts of benzene and toluene using a fuel gas containing C5 olefins at a temperature of about 315° C. to about 455° C., a pressure of about 2860 to about 3550 kPa (about 400 to about 800 psig), and for about 0.4 hours. -1 ~ approx. 0.8 hours -1 WHSV-Olefin, about 1 hour -1 ~ approx. 2 hours -1 alkylation to provide, among other things, mono- and dialkylates at reaction conditions including gas recycle of about 1.5 to 2.5 vol / vol of WHSV-reformate and a fuel gas feed of about 1.5 to 2.5 vol / vol; (4) alkylation of aromatic hydrocarbons such as, for example, benzene, toluene, xylene and naphthalene with long chain olefins such as, for example, C14 olefins, at reaction conditions including temperatures of about 160° C. to about 260° C. and pressures of about 2515 to 3205 kPa (350 to 450 psig) to provide alkylated aromatic lubricant base stocks; (5) Alkylation of phenol using an olefin or an equivalent amount of alcohol at a temperature of about 200°C to about 250°C, a pressure of about 1480 to 2170 kPa (200 to 300 psig), and for about 2 hours. -1 ~ approx. 10 hours -1 alkylation to provide long chain alkylphenols under reaction conditions containing a total WHSV of; (6) Alkylation of an isoalkane, such as isobutane, with an olefin, such as 2-butene, at a temperature of about -25°C to about 400°C, e.g., 75°C to 200°C, at a pressure of less than atmospheric pressure to about 35000 kPa (5000 psig), e.g., 100 to 7000 kPa (1 to 1000 psig), for about 0.01 hours. -1 ~ approx. 100 hours -1 , e.g. 0.1 hours -1 ~20 hours -1 and a molar ratio of total isoalkanes to total olefins of about 1:2 to about 100:1, e.g., 3:1 to 30:1. Includes. EXAMPLES
[0047] The present invention is further illustrated below, without being limited in scope by these. In these examples, X-ray diffraction (XRD) patterns of the as-synthesized materials were recorded on an X-ray powder diffractometer (Bruker, D8 Discover or STOE, Stadi P Combi) using copper K-α radiation in the 2θ range of 2–40 degrees. Scanning electron microscopy (SEM) images of the as-synthesized materials were obtained on a FEI Company, Helios Nanolab G3 UC scanning electron microscope. The zeolite framework type of the as-synthesized materials was identified by comparing their XRD patterns with those of known zeolite materials. SEM images were used to aid in the assessment of product purity, and the presence of distinctly different crystalline morphology structures in the SEM images may be indicative of impurities in the form of other crystalline materials. Such proximate analysis may be particularly useful in identifying the presence of relatively small amounts of crystalline impurity formation that may not be discernible in the product XRD pattern.
[0048] solid 27 Al MAS NMR spectra (1 pulse) were recorded on a Bruker Avance III-HD 500 spectrometer (11.7 T) operating at 130.3 MHz. Measurements were performed using a 4 mm outer diameter zirconia rotor spinning at 14 kHz. MAS NMR spectra were acquired with a π / 12 pulse and a 1 s recycle delay. Chemical shifts were referenced to a 1 M Al(NO3)3 solution. Samples were hydrated overnight prior to analysis. The density of the powder material was measured in its as-synthesized dry form using a pycnometer. The pycnometer was weighed empty and then filled with water to determine the exact volume. A precisely known amount of material was added to the pycnometer and then filled with water. The pycnometer was placed in an ultrasonic bath to remove any air trapped between the powder material. The material was allowed to sit until the top liquid was clear. The pycnometer was then filled with water and weighed. The volume of the powder was determined based on the mass difference and the density was calculated based on the mass and volume.
[0049] The following measurements were performed on the ion-exchanged and calcined samples. Each sample was subjected to ion-exchange and calcination using the following procedure: the as-prepared samples were washed twice with 1 M ammonium nitrate solution and then calcined at 537° C. for 10 hours. The SiO2:Al2O3 molar ratio of the materials was determined by inductively coupled plasma (ICP) method.
[0050] The total BET surface area of the material (S tot ) was determined using nitrogen adsorption-desorption at liquid nitrogen temperatures by the BET method described in S. Brunauer, PH Emmett and E. Teller, J. Am. Chem. Soc., 1938, 60, 309, which is incorporated herein by reference.
[0051] The micropore volume (V micro ) was determined by applying a t-plot model to the N2 isotherm as referenced in "Analytical Methods in Fine Particle Technology, PA Webb and C. Orr, Micrometrics Instrument Corporation, ISBN 0-9656783-0-X," the contents of which are incorporated herein by reference. Physical adsorption isotherms were collected according to the methods disclosed in "Analytical Methods in Fine Particle Technology", PA Webb and C. Orr, Micrometrics Instrument Corporation ISBN 0-9656783-0-X, the contents of which are incorporated herein by reference.
[0052] Comparative Examples 1 and 2 illustrate the preparation of MCM-49 and MCM-56 zeolites, respectively. Examples 3-5 illustrate the preparation of MWW framework type molecular sieves by the method of the present invention using various amounts of PDDA. Comparative Examples 6 and 7 were prepared by the synthesis method of Example 3, but in the presence of higher amounts of PDDA. Comparative Example 1 MCM-49 Zeolite A sodium aluminate solution was prepared by dissolving sodium aluminate powder in water (23.5% by weight alumina, 19.4% by weight sodium oxide). 18891.0 mg of water, 1192.4 mg of sodium aluminate solution, 89.6 mg of sodium hydroxide solution (40.0% by weight), 3779.3 mg of precipitated silica (Ultrasil® VN3), and 1047.7 mg of hexamethyleneimine solution (99.0% by weight) were added to a Teflon® liner. The mixture was stirred for 5 minutes after each addition and 10 minutes after the last addition. The mixture was then treated under hydrothermal conditions at 160° C. for 60 hours while stirring with a U-shaped impeller. The solid material was then collected, washed several times with water, and dried at 120° C. The synthesis mixture was as follows (synthesis mixture / molar ratio): Si / Al2:20.84, M / Si:0.15, R / Si:0.18, H2O / Si:19.02. Using XRD, the recovered material was identified as MCM-49.
[0053] Comparative Example 2 MCM-56 Zeolite A sodium aluminate solution was prepared by dissolving sodium aluminate powder in water (23.5% by weight alumina, 19.4% by weight sodium oxide). 18986.0 mg of water, 1332.1 mg of sodium aluminate solution, 183.8 mg of MCM-56 seeds (20.0% by weight), 3846.5 mg of precipitated silica (Ultrasil® VN3), and 651.6 mg of hexamethyleneimine solution (99.0% by weight) were added to a Teflon® liner. The mixture was stirred for 5 minutes after each addition and 10 minutes after the last addition. The mixture was then treated under hydrothermal conditions at 160° C. for 60 hours while stirring with a U-shaped impeller. The solid material was then collected, washed several times with water, and dried at 120° C. The synthesis mixture was as follows (synthesis mixture / molar ratio, excluding seed crystals): Si / Al2:19.01, M / Si:0.14, R / Si:0.11, H2O / Si:18.94. The amount of seed crystals used was 0.95 mass% [g 種晶 (g SiO2 +g Al2O3 ) -1 ] was the case.
[0054] Using XRD, the recovered material was identified as MCM-56.
[0055] Example 3 MWW type zeolite (0.10% by mass PDDA chloride) Sodium aluminate solution was prepared by dissolving sodium aluminate powder in water (10.1 wt.% alumina, 7.3 wt.% sodium oxide). 17097.3 mg water, 2784.5 mg sodium aluminate solution, 172.5 mg sodium hydroxide solution (40.0 wt.%), 125.0 mg PDDA chloride (average Mw 200,000-350,000, 20 wt.%), 3774.4 mg precipitated silica (Ultrasil® VN3), and 1046.3 mg hexamethyleneimine solution (99.0 wt.%) were added to a Teflon® liner. The mixture was stirred for 5 min after each addition, except for 15 min after the PDDA addition, and 10 min after the last addition. The mixture was then treated under hydrothermal conditions at 160° C. for 60 h with stirring using a U-shaped impeller. The solid material was then collected, washed several times with water and dried at 120°C.
[0056] The synthesis mixture was as follows (synthesis mixture / molar ratio): Si / Al2:20.84, M / Si:0.15, R / Si:0.18, H2O / Si:19.02. The amount of PDDA chloride used was 0.10 wt % based on the weight of the synthesis mixture. Using XRD, the recovered material was identified as MWW-type zeolite.
[0057] Example 4 MWW type zeolite (0.30% by mass PDDA chloride) Sodium aluminate solution was prepared by dissolving sodium aluminate powder in water (10.0 wt. % alumina, 7.3 wt. % sodium oxide). 16468.8 mg water, 2797.8 mg sodium aluminate solution, 172.1 mg sodium hydroxide solution (40.0 wt. %), 750.3 mg PDDA chloride (average Mw 200,000-350,000 g / mol, 10 wt. %), 3766.8 mg precipitated silica (Ultrasil® VN3), and 1044.2 mg hexamethyleneimine solution (99.0 wt. %) were added to a Teflon® liner. The mixture was stirred for 5 min after each addition, except for 15 min after the PDDA addition, and 10 min after the last addition. The mixture was then treated under hydrothermal conditions at 160° C. for 60 h with stirring using a U-shaped impeller. The solid material was then collected, washed several times with water and dried at 120°C. The synthesis mixture was as follows (synthesis mixture / molar ratio): Si / Al2:20.84, M / Si:0.15, R / Si:0.18, H2O / Si:19.02. The amount of PDDA chloride used was 0.30 wt % based on the weight of the synthesis mixture. Using XRD, the recovered material was identified as MWW-type zeolite.
[0058] Example 5 MWW type zeolite (0.70% by mass PDDA chloride) Sodium aluminate solution was prepared by dissolving sodium aluminate powder in water (10.1 wt.% alumina, 7.3 wt.% sodium oxide). 16394.0 mg water, 2767.8 mg sodium aluminate solution, 171.4 mg sodium hydroxide solution (40.0 wt.%), 875.0 mg PDDA chloride (average Mw 200,000-350,000, 20 wt.%), 3751.7 mg precipitated silica (Ultrasil® VN3), and 1040.0 mg hexamethyleneimine solution (99.0 wt.%) were added to a Teflon® liner. The mixture was stirred for 5 min after each addition, except for 15 min after the PDDA addition, and 10 min after the last addition. The mixture was then treated under hydrothermal conditions at 160° C. for 60 h with stirring using a U-shaped impeller. The solid material was then collected, washed several times with water and dried at 120°C. The synthesis mixture was as follows (synthesis mixture / molar ratio): Si / Al2:20.84, M / Si:0.15, R / Si:0.18, H2O / Si:19.02. The amount of PDDA chloride used was 0.70 wt % based on the weight of the synthesis mixture. Using XRD, the recovered material was identified as MWW-type zeolite.
[0059] Comparative Example 6 (1.00% by mass PDDA chloride) Sodium aluminate solution was prepared by dissolving sodium aluminate powder in water (10.1 wt. % alumina, 7.3 wt. % sodium oxide). 16042.3 mg water, 2759.4 mg sodium aluminate solution, 170.9 mg sodium hydroxide solution (40.0 wt. %), 1250.0 mg PDDA chloride (average Mw 200,000-350,000, 20 wt. %), 3740.4 mg precipitated silica (Ultrasil® VN3), and 1036.9 mg hexamethyleneimine solution (99.0 wt. %) were added to a Teflon® liner. The mixture was stirred for 5 min after each addition, except for 15 min after the PDDA addition, and 10 min after the last addition. The mixture was then treated under hydrothermal conditions at 160° C. for 60 h with stirring using a U-shaped impeller. The solid material was then collected, washed several times with water and dried at 120°C. The synthesis mixture was as follows (synthesis mixture / molar ratio): Si / Al2:20.84, M / Si:0.15, R / Si:0.18, H2O / Si:19.02. The amount of PDDA chloride used was 1.00 wt % based on the weight of the synthesis mixture. The MWW phase did not crystallize at a PDDA chloride concentration of 1.00 wt %.
[0060] Comparative Example 7 (2.00% by mass PDDA chloride) Sodium aluminate solution was prepared by dissolving sodium aluminate powder in water (10.1 wt. % alumina, 7.3 wt. % sodium oxide). 14870.2 mg water, 2731.6 mg sodium aluminate solution, 169.2 mg sodium hydroxide solution (40.0 wt. %), 2500.0 mg PDDA chloride (average Mw 200,000-350,000, 20 wt. %), 3702.6 mg precipitated silica (Ultrasil® VN3), and 1026.4 mg hexamethyleneimine solution (99.0 wt. %) were added to a Teflon® liner. The mixture was stirred for 5 min after each addition, except for 15 min after the PDDA addition, and 10 min after the last addition. The mixture was then treated under hydrothermal conditions at 160° C. for 60 h with stirring using a U-shaped impeller. The solid material was then collected, washed several times with water and dried at 120°C. The synthesis mixture was as follows (synthesis mixture / molar ratio): Si / Al2:20.84, M / Si:0.15, R / Si:0.18, H2O / Si:19.02. The amount of PDDA chloride used was 2.00 wt % based on the weight of the synthesis mixture. The MWW phase did not crystallize at a PDDA chloride concentration of 2.00 wt %.
[0061] Analysis of crystalline material products FIG. 1 shows the XRD spectra of Comparative Examples 1-2 and Examples 3-5 in their as-synthesized forms. The XRD pattern of Comparative Example 1 shows typical peaks of MCM-49; the XRD pattern of Comparative Example 2 shows typical peaks of MCM-56; and the XRD patterns of Examples 3-5 show typical peaks of MWW framework type molecular sieves. Compared to the XRD pattern of Comparative Example 1 (MCM-49), the XRD pattern of Comparative Example 2 (MCM-56) shows broader and often overlapping peaks. Without wishing to be bound by theory, it is believed that these differences are indicative of a predominance of disordered layered bodies in MCM-56 compared to the more regularly stacked layers present in MCM-49. Most notably, the XRD pattern of the MCM-49 material shows two clearly distinguishable separate peaks around 8 and 10 (2θ), while the XRD pattern of MCM-56 shows a broad merged peak in the same region (as shown by comparison of the XRD spectra for Comparative Examples 1 and 2). For a more detailed discussion of the characteristic XRD pattern of MCM-56 compared to, for example, MCM-49, see U.S. Pat. Nos. 5,362,697, 5,827,491, and 5,453,554, the contents of which are incorporated herein by reference. The XRD patterns of Examples 3 and 4 are similar to that of MCM-49 (Comparative Example 1). The XRD pattern of Example 5 shows a broader peak compared to Examples 3-4. The XRD patterns of Comparative Examples 1-2 and Examples 3-5 also show that no impurity phases are detected.
[0062] 2a-2e show scanning electron microscope (SEM) images of Comparative Examples 1-2 and Examples 3-5, respectively. The SEM images show that the morphology of Examples 3 and 4 is similar to that of MCM-49 (Comparative Example 1). For Example 5, the SEM images show some small amount of amorphous phase, so without being bound by theory, it is believed that the crystallization time is extended at higher PDDA concentrations, as higher PDDA concentrations may inhibit or slow down crystallization. No changes in morphology, for example due to the presence of impurities and / or amorphous phases, are visible in the SEM images of any of the examples. Thus, for all examples, the SEM analysis suggests the formation of a single zeolite structure.
[0063] FIG. 3 shows Comparative Examples 1 to 2 and Example 4. 27 Al NMR spectra are shown. In all spectra, substantial peaks are seen around 50 ppm. The chemical shifts (δ) close to 50 ppm are characteristic of Al incorporated into the zeolite framework. None of the spectra show a peak in the region around 0 ppm, which is indicative of Al outside the framework. Therefore, 27 Al NMR spectroscopy suggests that the Al detected by ICP-OES analysis is framework Al, indicating that the method of the present invention successfully incorporated Al into the zeolite framework.
[0064] 4 shows the N2 physical adsorption isotherms of Comparative Examples 1-2 and Example 4 after ion exchange and calcination. The physical adsorption isotherm of Comparative Example 1 (MCM-49) shows a strong hysteresis loop, which is about 4.8 p / p 0 The physisorption isotherm differs from that of Comparative Example 2 (MCM-56) in that it rejoins the initial curve at p / p 0As the σ changes from 1 back to 0, it is believed to be an indication of a significant slowing in the desorption of N2 from the zeolite and evidence that MCM-56 has a different mesopore shape than that of MCM-49. As can be seen from Figure 4, the N2 physisorption isotherm of Example 4 is more similar to that of MCM-56 (Comparative Example 2). Thus, it is believed that the mesopore shape of the MWW molecular sieve of Example 4 is more similar to that of MCM-56.
[0065] Figure 5 shows the as-prepared thermogravimetric analysis of Comparative Example 1 and Example 4. From Figure 5, it can be seen that Example 4 has about 2 wt% higher mass loss compared to Comparative Example 1, which can be attributed to the decomposition of PDDA at 400-600 °C. Table 3 shows the Si:Al2 molar ratios after ion exchange and calcination, as well as the textural and chemical properties (total surface area, mesopore surface area, ratio of mesopore surface area to total surface area, and micropore volume) after ion exchange and calcination for Comparative Examples 1-2 and Examples 3-5. [Table 3] As shown by the results in Table 3, Examples 3-4 are characterized by a high external surface area (or mesopore surface area) combined with a high micropore volume. More specifically, the total surface area (S tot ) and external surface area (S ext ) is significantly higher than the total and external surface areas of MCM-49 and MCM-56 (Comparative Examples 1-2), while the S ext / S tot The ratio is S of MCM-56 (Comparative Example 2) ext / S tot The ratio is close to that of MCM-49 (Comparative Example 1), while the micropore volume of Examples 3-4 is maintained and is closer to that of MCM-49 (Comparative Example 1). microThe values may be due to some small amount of amorphous phase present in the product. As previously mentioned, without being bound by theory, it is believed that at higher PDDA concentrations, crystallization times are extended because higher PDDA concentrations may inhibit or slow down crystallization.
[0066] In summary, the presence of PDDA in the synthesis mixture is accompanied by changes in total surface area, external surface area (or mesopore surface area) and microporosity, providing MWW framework type molecular sieves with a layered structure that exhibits an increase in total surface area and an increase in external surface area (or mesopore surface area) while retaining or increasing microporosity. This is particularly advantageous since the accessibility of the surface pockets of MWW type molecular sieves is of great importance for their catalytic performance, for example in applications such as aromatic alkylation, while the retention or increase of microporosity is fundamental to shape the selective catalysis by molecular sieves.
[0067] (Comparative Example 8 and Example 9) Compounded extrudates containing molecular sieves prepared according to Comparative Example 1 and Example 4 A portion of Comparative Example 1 and Example 4 were formed into 1 / 20 inch four-lobe extrudates corresponding to Comparative Example 8 and Example 9 by the following method. Eighty (80) parts by weight of zeolite (Comparative Example 1, Example 4, respectively) were combined with 20 parts of Versal-300 alumina on a dry weight basis to form a dry powder. The dry powder was placed in a grinder or mixer and mixed for about 5-15 minutes. During the mixing process, sufficient water was added to the powder to produce an extrudable paste. The extrudable paste was formed into 1 / 20 inch four-lobe extrudates using a ram extruder. After extrusion, the 1 / 20 inch four-lobe extrudates were dried at a temperature of about 120° C. The dried extrudates were then calcined in nitrogen at a temperature of 454° C. to 593° C. and cooled under a nitrogen stream. The extrudates were then loaded into an exchange column, humidified, and exchanged with ammonium nitrate. After washing the extrudates with water, they were calcined at 454°C-593°C under air flow.
[0068] The dried extrudates were tested for collidine uptake by the following method. Collidine uptake of the extruded zeolite composition was determined by a thermogravimetric analyzer as micromoles of collidine (a type of catalyst poison) absorbed per gram of composition sample dried under nitrogen flow at 200° C. for 60 minutes. After the catalyst sample was dried, collidine was sparged onto the catalyst sample for 60 minutes at a collidine partial pressure of 3 Torr. The sample was then flushed with nitrogen for 60 minutes. Collidine uptake was calculated from the following formula: (sample mass after sparging with collidine-dried catalyst sample mass)÷(molecular weight of collidine×dried catalyst sample mass). When the sample mass and dried sample mass are measured in grams, the molecular weight of collidine is 121.2×10 per micromoles. -4 grams.
[0069] Table 4 shows the measured collidine incorporation of the extrudates of Comparative Example 8 and Example 9. Because collidine (2,4,6-trimethylpyridine) is a relatively large molecule with an aromatic ring core, the collidine incorporation may provide an indication of the proportion of acid sites located in the mesopores that are accessible to larger molecules. It is believed that catalysts that exhibit high collidine incorporation tend to be more effective at alkylating larger molecules, especially single ring aromatic molecules. Having a greater number of surface acid sites accessible to larger molecules may allow the catalyst to continue to provide an acceptable level of activity for a longer period of time. [Table 4]
[0070] As shown by the results in Table 4, collidine incorporation is significantly higher in Example 9 versus Comparative Example 8. This may correlate with the greater mesoporosity for the MWW framework type molecular sieves of the present invention (exemplified by Example 4) compared to the MCM-49 material (exemplified by Comparative Example 1). This is also representative of an increased proportion of acid sites located in the mesopores that are accessible to larger molecules, and improved alkylation activity for larger molecules, particularly single ring aromatic molecules. The dried extrudates were also tested for benzene alkylation activity and selectivity by the following method: 0.5 g of catalyst extrudate was placed in an isothermal, well-mixed Parr autoclave reactor under nitrogen atmosphere with a mixture containing 156 g benzene and 28 g propylene. The reaction was carried out at 130° C. and 2170 kPa (300 psig) for 4 hours under nitrogen atmosphere. Small samples of the product were removed at regular intervals and analyzed by gas chromatography. The catalyst performance was evaluated by the kinetic activity rate constant based on propylene conversion and isopropylbenzene (cumene) selectivity at 100% propylene conversion.
[0071] Table 5 shows the catalytic properties of the extrudates of Comparative Example 8 and Example 9, in particular the pseudo second order rate constant (k), the selectivity of di-isopropylbenzene to isopropylbenzene (cumene) (S DIPB / IPB ) and the selectivity of tri-isopropylbenzene to isopropylbenzene (cumene) (S TIPB / IPB ) is shown. [Table 5]
[0072] As can be seen from Table 5, the inventive extrudates of Example 9 exhibit significantly lower selectivity to the undesired di- and tri-isopropylbenzene by-products compared to the extrudates of Comparative Example 8 based on MCM-49, while the second order rate constants (k) remain similar. Although the invention has been described and illustrated with reference to specific embodiments, those skilled in the art will recognize that the invention also lends itself to many different variations not specifically exemplified herein. In the above description, where integers or elements having known, obvious or foreseeable equivalents are mentioned, such equivalents are incorporated herein as if individually set forth. To determine the true scope of the present invention, reference should be made to the claims, which should be construed to encompass any such equivalents. The reader will also understand that integers or features of the present invention described as preferred, advantageous, convenient, etc. are optional and do not limit the scope of the independent claims. Moreover, it will be understood that any such integers or features may be beneficial in some embodiments of the present invention, while in other embodiments they may be undesirable and therefore may not be present. All numerical values within the detailed description of this specification are modified by the value indicated by "about" to account for experimental error and variation expected by those skilled in the art. Additionally or alternatively, the present invention relates to:
[0073] Embodiment 1: A process for preparing a synthesis mixture capable of forming a molecular sieve of MWW framework type, the synthesis mixture comprising water, a source of silicon, a source of a trivalent element X, a structure directing agent R, a source of an alkali metal or alkaline earth metal cation M, a source of poly(diallyldimethylammonium) cation (PDDA), optionally a source of a pentavalent element Z, optionally a source of hydroxide ions, optionally a seed crystal, the synthesis mixture having the following molar ratio composition: Si:X2=8~30 or less H2O:Si=5~50 or less M:Si=0.05-1.0, R:Si=0.05~1.0 having a source of PDDA is added in an amount of less than 0.01 to 1.0 weight percent based on the weight of the synthesis mixture; b) heating said synthesis mixture under crystallization conditions for a time sufficient to form crystals of said MWW framework-type molecular sieve, said crystallization conditions comprising a temperature between 80° C. and 225° C.; c) recovering said crystals of MWW framework type molecular sieve from the synthesis mixture; A method for synthesizing MWW framework type molecular sieves comprising: Embodiment 2: The method of embodiment 1, wherein the source of PDDA is selected from at least one of PDDA chloride and PDDA hydroxide, in particular PDDA chloride.
[0074] Embodiment 3: The method of embodiment 1 or 2, wherein the synthesis mixture contains the PDDA source in an amount of 0.05-0.7% by weight, preferably less than 0.05-0.7%, based on the weight of the synthesis mixture. Embodiment 4: The method of any one of embodiments 1 to 3, wherein the structure directing agent R is selected from the group consisting of cyclopentylamine, cyclohexylamine, cycloheptylamine, hexamethyleneimine (HMI), heptamethyleneimine, homopiperazine, pentamethonium bromide or hydroxide, hexamethonium bromide or hydroxide, heptamethonium bromide or hydroxide, and combinations thereof, preferably wherein the structure directing agent R is hexamethonium imine (HMI). Embodiment 5: The method of any one of embodiments 1-4, wherein X is selected from the group consisting of aluminum, boron, gallium, and mixtures thereof, preferably X comprises at least aluminum, more preferably X is aluminum.
[0075] Embodiment 6: The method of any one of embodiments 1 to 5, wherein the source of trivalent element X comprises Al2O3, preferably the source of trivalent element X is Al2O3. Embodiment 7: The method of any one of embodiments 1-6, wherein the silicon source comprises SiO2, preferably the silicon source is SiO2. Embodiment 8: The method of any one of embodiments 1-7, wherein Z, if present, is phosphorus. Embodiment 9: The method of any one of embodiments 1 to 7, wherein the synthesis mixture does not contain a pentavalent element Z. Embodiment 10: The method of any one of embodiments 1 to 9, wherein M is selected from the group consisting of sodium, potassium, lithium, rubidium, calcium, magnesium and mixtures thereof, preferably sodium and / or potassium, more preferably sodium.
[0076] Embodiment 11: The method of any one of embodiments 1 to 10, wherein the synthesis mixture comprises a cation M source of an alkali metal or an alkaline metal or an alkaline earth metal, in a M:Si molar ratio of 0.08 to 0.5, more particularly 0.1 to 0.3, such as greater than 0.1 and less than 0.18. Embodiment 12: OH - 12. The method of any one of the preceding embodiments, wherein the source, when present, comprises an alkali metal hydroxide, an alkaline earth metal hydroxide, ammonium hydroxide, aluminum hydroxide, the hydroxide form of structure directing agent R, the hydroxide form of PDDA, or a combination thereof.
[0043] Embodiment 13: The synthesis mixture may comprise a source of hydroxide ions in an amount of 0.05 to 1.0, preferably 0.08 to 0.5, more preferably 0.1 to 0.3, such as 0.1 to 0.25 OH - 13. The method of any one of embodiments 1 to 12, comprising a molar ratio of :Si. Embodiment 14: The method of any one of embodiments 1 to 13, wherein the synthesis mixture comprises R and M in an R:M molar ratio of less than 2.5, preferably less than 2.0.
[0043] Embodiment 15: The synthesis mixture comprises a molecular sieve seed crystal in an amount of 0.05 to 2 g. 種晶 / g (silicon source+source of trivalent element X).
[0077] Embodiment 16: The method of embodiment 15, wherein the seed crystals comprise MWW framework type molecular sieves, preferably MCM-49 and / or MCM-56. Embodiment 17: The method of any one of embodiments 1 to 16, wherein the crystallization conditions in step (b) comprise a temperature from 100°C to 200°C, preferably from 140°C to 180°C.
[0078] Embodiment 18: The method of any one of embodiments 1 to 17, wherein the crystallization conditions in step (b) comprise heating for a period of from 1 to about 800 hours, particularly from about 10 to less than 600 hours, particularly from about 24 to 140 hours, for example from about 60 to about 90 hours. Embodiment 19: A molecular sieve of MWW framework type obtainable by the method of any one of embodiments 1 to 18.
[0079] Embodiment 20: A molecular sieve of MWW framework type, in its calcined anhydrous form: Molar Relationships: (n)SiO2:X2O3 wherein X is a trivalent element selected from the group consisting of aluminum, boron, gallium, and mixtures thereof, preferably X includes at least aluminum, more preferably X is aluminum, and n is the number of moles of SiO2 per mole of X2O3, varying from 8 to less than 30; At least 125m 2 External surface area (S ext ); and 0.13cm 3 / g or more for micropore volume (V micro ) A molecular sieve having
[0080] Embodiment 21: A ratio of the external surface area to the total BET surface area (S ext / S tot 21. The molecular sieve of embodiment 19 or 20, having a molecular weight of 1.0 or more,
[0081] Embodiment 22: Use of the molecular sieve of any one of embodiments 19 to 21 in a hydrocarbon chemical conversion process, particularly in a process where the hydrocarbon chemical conversion process is an alkylation reaction, more particularly an aromatic alkylation.
Claims
1. a) preparing a synthesis mixture capable of forming a molecular sieve of MWW framework type, said synthesis mixture comprising water, a silicon source, a source of trivalent element X, a structure directing agent R, a source of alkali metal or alkaline earth metal cation M, a source of poly(diallyldimethylammonium) cation (PDDA), said synthesis mixture having the following molar ratio composition: Si:X 2 = 8 to less than 30, H 2 O: Si=5 to less than 50, M: Si=0.05-1.0, R: Si=0.05~1.0 having A source of PDDA is added in an amount of 0.01 to less than 1.0 wt. % based on the weight of the synthesis mixture; b) heating said synthesis mixture under crystallization conditions for a time sufficient to form crystals of said MWW framework type molecular sieve, said crystallization conditions comprising a temperature of from 80° C. to 225° C.; c) recovering said crystals of MWW framework type molecular sieve from the synthesis mixture; A method for synthesizing a MWW framework type molecular sieve comprising:
2. 2. The method according to claim 1, wherein the PDDA source is selected from at least one of PDDA chloride and PDDA hydroxide, in particular PDDA chloride, and the PDDA source is added to the synthesis mixture in an amount of 0.05 to 0.7% by weight, preferably less than 0.05 to 0.7%, based on the weight of the synthesis mixture.
3. 3. The method according to claim 1 or 2, wherein the structure directing agent R is selected from the group consisting of cyclopentylamine, cyclohexylamine, cycloheptylamine, hexamethyleneimine (HMI), heptamethyleneimine, homopiperazine, pentamethonium bromide or hydroxide, hexamethonium bromide or hydroxide, heptamethonium bromide or hydroxide, and combinations thereof, preferably the structure directing agent R is hexamethonium imine (HMI).
4. X is selected from the group consisting of aluminum, boron, gallium, and mixtures thereof, preferably X comprises at least aluminum, more preferably X is aluminum; in particular, the source of the trivalent element X is Al 2 O 3 and preferably the source of the trivalent element X is Al 2 O 3 The method according to claim 1 or 2,
5. The silicon source is SiO 2 and preferably the silicon source is SiO 2 The method according to claim 1 or 2, 6. The method of claim 1 or 2, wherein the synthesis mixture further comprises a source of a pentavalent element Z, preferably phosphorus.
7. The method of claim 1, wherein the synthesis mixture does not contain the pentavalent element Z.
8. 3. The method according to claim 1 or 2, wherein M is selected from the group consisting of sodium, potassium, lithium, rubidium, calcium, magnesium and mixtures thereof, preferably sodium and / or potassium, more preferably sodium; in particular, the synthesis mixture comprises a source of alkali metal or alkaline earth metal cation M in a M:Si molar ratio of 0.08 to 0.5, more particularly 0.1 to 0.3, such as greater than 0.1 and less than 0.
18.
9. The synthesis mixture further comprises a source of hydroxide ions, preferably OH. - The source may comprise an alkali metal hydroxide, an alkaline earth metal hydroxide, ammonium hydroxide, aluminum hydroxide, the hydroxide form of Structure Directing Agent R, the hydroxide form of PDDA, or a combination thereof, in particular where the synthesis mixture comprises a source of hydroxide ions having an OH concentration of 0.05 to 1.0, preferably 0.08 to 0.5, more preferably 0.1 to 0.3, such as 0.1 to 0.
25. - The method according to claim 1 or 2, comprising the steps of:
10. 3. The process according to claim 1 or 2, wherein the synthesis mixture comprises R and M in an R:M molar ratio of less than 2.5, preferably less than 2.
0.
11. The synthesis mixture contains 0.05 to 2 g of molecular sieve seed crystals. 種晶 3. The method of claim 1 or 2, further comprising: / g (silicon source + source of trivalent element X), preferably the seed crystals comprise a molecular sieve of MWW framework type.
12. 3. The process according to claim 1 or 2, wherein the crystallization conditions in step (b) comprise a temperature of from 100° C. to 200° C., preferably from 140° C. to 180° C., and the crystallization conditions in step (b) comprise heating for a period of from 1 to about 800 hours, in particular from about 10 to less than 600 hours, in particular from about 24 to 140 hours, for example from about 60 to about 90 hours.
13. A molecular sieve of MWW framework type obtainable by the method according to any one of claims 1 to 12.
14. A molecular sieve of the MWW framework type, which in its calcined anhydrous form has the molar relationship: (n)SiO 2 :X 2 O 3 wherein X is a trivalent element selected from the group consisting of aluminum, boron, gallium, and mixtures thereof; preferably, X comprises at least aluminum; more preferably, X is aluminum; and n is X 2 O 3 per mole of SiO 2 where n varies from 8 to less than 30); 2 / g of external surface area (S ext ) and 0.13 cm 3 / g or more of micropore volume (V micro ) A molecular sieve having
15. A ratio of external surface area to total BET surface area (S ext / S tot 15. The molecular sieve of claim 13 or 14, having a molecular weight of 1:1 or more.
16. 15. Use of the molecular sieve according to claim 13 or 14 in a hydrocarbon chemical conversion process, in particular in a process where the hydrocarbon chemical conversion process is an alkylation reaction, more particularly an aromatic alkylation.